British military women: combat exposure, deployment and mental health. (12th August 2019) - Jones, N; Greenberg, N; Phillips, A; Simms, A; Wessely, S
Abstract: Background: Internationally, women are about to undertake combat duties alongside their male colleagues. The psychological effect of this policy change is largely unknown. Aims: To explore the mental health impact of combat exposure among military women. Methods: Self-report, between-subjects survey data were collected in Iraq and Afghanistan on four occasions between 2009 and 2014 ( n = 4139). Differences in mental health, stigmatization, deployment experiences, intimate relationship impact, perception of family support levels, unit cohesion, leadership and help-seeking were compared between deployed men and women. Comparisons were repeated with the study sample stratified by level of combat exposure. Outcomes were examined using logistic regression adjusted for socio-demographic, mental health and military factors. Results: Overall, 4.1% of women and 4.3% of men reported post-traumatic stress disorder (PTSD) (odds ratio (OR) 1.31, 95% confidence interval (95% CI) 0.70–2.46); 22% of women and 16% of men reported symptoms of common mental disorder (CMD) (OR 1.52, 95% CI 1.11–2.08). Women were less likely to report mental health-related stigmatization (OR 0.68, 95% CI 0.53–0.87), negative relationship impact from deployment (OR 0.69, 95% CI 0.49–0.98) and subjective unit cohesion (OR 0.69, 95% CI 0.53–0.90). Help-seeking for emotional problems was similar by gender (OR 1.22, 95% CI 0.84–1.77). Overall, outcomes were minimally impacted by level of combat exposure. Conclusions: Although women experienced more CMD symptoms, PTSD symptoms were similar by gender. Subject to confirmation of the study findings, women may not require enhanced mental healthcare during deployment for exposure-based conditions such as PTSD when undertaking the ground close combat role.